The student's guide to writing : - Peck, John (Palgrave Macmillan, 2005)
The new edition of this best-seller guides students through the process of improving their writing, showing them how to construct a sentence, a paragraph and an essay. The authors have revised the original edition to make their explanations even clearer, included a "Spot the Mistake" section, and added an index for easier navigation. Explaining grammar, punctuation and spelling, it is carefully designed for students who need reminding of the basic rules of English and wish to perfect their writing. This is the most indispensable, up-to-date handbook that should be on every student's desk.